Preparation And Properties Of Rubber Seed Shell Flour (Rssf)- Filled Polypropylene (Pp) Composites - Shafiq, Mohamad Danial (2014)
In this research, rubber seed shell flour (RSSF) was incorporated in polypropylene (PP) to determine the composites with optimum properties. RSSF loadings were varied from 10 php to 40 php to study the effect of adding RSSF on processing, tensile, morphological, flexural, impact, water absorption and thermal properties of PP/RSSF composites. In the second series, the effect of adding polyethylene copolymerized with acrylic acid (PE-co-AA) was studied, on the properties of PP/RSSF composites. Phthalic anhydride (PA) was added as a compatibilizer separately in PP/RSSF composites in the third series. In the next series, epoxidized vegetable oil (EVO) was added as a compatibilizer in PP/RSSF with fixed amount of 7 php. Preparation of the composites has been conducted in Haake Polydrive internal mixer with the temperature of 180oC using rotor speed of 50 rpm. The addition of RSSF in the composites increased the stabilization torque in PP composites. Furthermore, compatibilization of PP/RSSF composites with PE-co-AA and PA increased the stabilization torque of PP/RSSF. Somehow, the presence of EVO reduced the stabilization torque resulted from flexible and long chain of EVO. The addition of RSSF in PP reduced the tensile strength and elongation at break, somehow, the Young’s modulus is improved. This is mainly caused by incompatibility of PP and RSSF resulted to poor interfacial adhesion. Clear observations were presented in SEM micrograph of tensile fracture surface. The incorporation of RSSF in PP has increased the water absorption of the composites due to the presence of lignocelluloses in RSSF, which possibly creates hydrogen bonding with water. Thermal properties of PP is improved with the presence of RSSF. Tensile, flexural and impact properties of the composites were improved with the presence of PE-co-AA, PA and EVO. It is mainly due to the improvement in interfacial adhesion, promoted by secondary chemical bonding between functional groups in compatibilizers and RSSF. Reduction in water absorption of the compatibilized composites was observed and it is caused by reduction of micro voids resulted from improvement in interfacial bonding. Thermal properties of PE-co-AA and EVO-compatibilized PP/RSSF are deteriorated due to thermal instability at higher temperature.